Hemostatic Biomarkers and Venous Thromboembolism Are Associated With Mortality and Response to Chemotherapy in Patients With Pancreatic Cancer. Issue 11 (November 2021) - Moik, Florian; Prager, Gerald; Thaler, Johannes; Posch, Florian; Wiedemann, Sarah; Schramm, Theresa; Englisch, Cornelia; Mackman, Nigel; Pabinger, Ingrid; Ay, Cihan
Abstract : Objective: Pancreatic cancer activates coagulation and increases risk of venous thromboembolism (VTE). We aimed at characterizing the association of hemostatic biomarkers and VTE with mortality and chemotherapy response. Approach and Results: Pancreatic cancer patients (N=145) were included in a prospective, observational cohort study (CATS [Vienna Cancer and Thrombosis Study]). Hemostatic biomarkers (D-dimer, extracellular vesicle–tissue factor activity, prothrombin fragment 1+2, fibrinogen, factor VIII, PAI-1 [plasminogen activator inhibitor 1], sP-selectin [soluble P-selectin], thrombin generation assay) were measured at inclusion. The impact of VTE on overall survival/progression-free survival (OS/PFS) was evaluated by multistate modeling. The association of biomarkers with OS was analyzed by Cox-regression and with PFS and disease control rate in patients initiating palliative chemotherapy (n=95) by Cox-regression and logistic regression. Multivariable analysis included stage, grade, sex, age, performance status, VTE (time-dependent), vascular infiltration/compression, and tumor marker levels (carbohydrate-antigen 19-9, carcinoembryonic antigen). VTE occurrence was associated with shorter OS (transition hazard ratio, 3.40 [95% CI, 2.05–5.64]) and shorter PFS (transition hazard ratio, 2.10 [1.16–3.79]). Median post-VTE OS/PFS in months was 5.5 [2.2–6.5] and 3.0 [1.5–3.9], compared with 13.4 [9.7–16.6] and 7.5 [5.9–9.8] in patients without VTE (both P <0.001). D-dimer, extracellular vesicle–tissue factor activity, PAI-1, and sP-selectin were associated with increased mortality (hazard ratio per doubling, 1.27 [1.00–1.61]; 1.63 [1.14–2.36]; 1.25 [1.06–1.47]; 1.52 [1.05–2.20]). In patients initiating palliative chemotherapy, higher D-dimer predicted shorter PFS (hazard ratio per doubling, 1.27 [1.01–1.60]) and lower disease control rate (odds ratio per doubling, 0.59 [0.36–0.98]). Conclusions: VTE diagnosis is associated with shorter OS and PFS. Higher baseline levels of D-dimer, extracellular vesicle–tissue factor activity, PAI-1, and sP-selectin were independently prognostic for increased mortality, and D-dimer predicted response to palliative chemotherapy. Abstract : Supplemental Digital Content is available in the text.